1998
DOI: 10.1111/j.1440-1746.1998.tb00738.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of autonomic nervous activity during gastrointestinal endoscopy: Analysis of blood pressure variability by tonometry

Abstract: We continuously measured blood pressure by tonometry in 30 patients during endoscopy to determine the influence of upper gastrointestinal endoscopy on cardiac events. Patients were divided into two groups: one group treated with scopolamine butylbromide as premedication (SB group) and another group without premedication (C group). Time- and frequency domain analyses of beat-to-beat systolic blood pressure variability were performed for 128 consecutive beats. For time-domain analysis, we calculated the coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…We have shown that older subjects tend to have a sustained increase in blood pressure throughout the procedure whilst younger patients have an increase at intubation but return to baseline within 1 min. These findings of two different types of response are in keeping with the results of the one previous study of blood pressure during gastroscopy [10]. However, our study suggests that these differences are related to advancing age and not premedication as previously suggested.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…We have shown that older subjects tend to have a sustained increase in blood pressure throughout the procedure whilst younger patients have an increase at intubation but return to baseline within 1 min. These findings of two different types of response are in keeping with the results of the one previous study of blood pressure during gastroscopy [10]. However, our study suggests that these differences are related to advancing age and not premedication as previously suggested.…”
Section: Discussionsupporting
confidence: 68%
“…In approximately two thirds of subjects there was an initial increase in blood pressure at intubation, after which the blood pressure returned to baseline within 1 min. In the remaining one third, the blood pressure elevation was sustained throughout the procedure [10]. The authors of this study attributed these different blood pressure responses to the use of premedication and resting the patient prior to the procedure.…”
Section: Introductionmentioning
confidence: 91%
“…[11][12][13][14]16,17 The ratio of LF power to HF power (LF power/HF power) has been reported to correlate with the level of sympathetic nervous activity. [11][12][13][14]16,18 We converted HF power data to a logarithmic scale to make it possible to analyze with linear regression. Changes in the parameters (∆LF power/HF power and ∆log HF power) were calculated using the following equation: (values during the endoscopy or at the completion)-(values before the endoscopy).…”
Section: Psa Of Heart-rate Variationsmentioning
confidence: 99%
“…Recently, quantitative evaluation of autonomic nervous functions has become possible by PSA of heart-rate variability during endoscopic procedures. [11][12][13][14] Patients and methods…”
Section: Introductionmentioning
confidence: 99%
“…To measure BP, a tonometric pulse pressure wave sensor was placed on the radial artery, and the beat-to-beat BP was noninvasively monitored. [9][10][11] The pulse pressure sensor consists of 30 elements; it facilitates measurement of BP per beat by automatically correcting the element pulse pressure in each position and the BP measured by the oscillometric method.…”
Section: Tonometric Measurement Of Bp and Ecg Monitoringmentioning
confidence: 99%